Addressing the Severity and Intensity of Poverty in Sub-Saharan Africa: How Relevant is the ICT and Financial Development Pathway? - Isaac K. Ofori; Mark K. Armah; Francis Taale; Pamela E. Ofori (Heliyon Business and Economics, 2021)
The study examines the effectiveness of financial development, financial access, and ICT diffusion in reducing the severity and intensity of poverty in Sub-Saharan Africa (SSA). Using data from the World Bank's World Development Indicators, and the Global Consumption and Income Project (1980–2019), we provide evidence robust to several specifications from the dynamic system GMM and the panel corrected standard errors estimation techniques to show that, compared to financial access, ICT usage, and ICT access, ICT skills is remarkable in reducing both the severity and intensity of poverty. The results further unveil that, though ICT skills reduce the intensity and severity of poverty in SSA, the effect is more pronounced in the presence of enhanced financial development and financial access. Policy recommendations are provided in line with the region's green growth agenda and the rise in technological hubs of the region.
Keywords: C33; D31; F63; I3; O33; O55; 330; Financial Access; Financial Development; ICTs; Inequality; Poverty; Africa